Inhibition of Neutrophils by Hypertonic Saline Involves Pannexin-1, CD39, CD73, and Other Ectonucleotidases. Issue 3 (September 2015) - Chen, Yu; Bao, Yi; Zhang, Jingping; Woehrle, Tobias; Sumi, Yuka; Ledderose, Stephan; Li, Xiaoou; Ledderose, Carola; Junger, Wolfgang G.
<x xml:space="preserve">Abstract</x> ABSTRACT Hypertonic saline (HS) resuscitation has been studied as a possible strategy to reduce polymorphonuclear neutrophil (PMN) activation and tissue damage in trauma patients. Hypertonic saline blocks PMNs by adenosine triphosphate (ATP) release and stimulation of A2a adenosine receptors. Here, we studied the underlying mechanisms in search of possible reasons for the inconsistent results of recent clinical trials with HS resuscitation. Purified human PMNs or PMNs in whole blood were treated with HS to simulate hypertonicity levels found after HS resuscitation (40 mmol/L beyond isotonic levels). Adenosine triphosphate release was measured with a luciferase assay. Polymorphonuclear neutrophil activation was assessed by measuring oxidative burst. The pannexin-1 (panx1) inhibitor 10panx1 and the gap junction inhibitor carbenoxolone (CBX) blocked ATP release from PMNs in purified and whole blood preparations, indicating that HS releases ATP via panx1 and gap junction channels. Hypertonic saline blocked N-formyl-Met-Leu-Phe–induced PMN activation by 40% in purified PMN preparations and by 60% in whole blood. These inhibitory effects were abolished by 10panx1 but only partially reduced by CBX, which indicates that panx1 has a central role in the immunomodulatory effects of HS. Inhibition of the ectonucleotidases CD39 and CD73 abolished the suppressive effect of HS on purified PMN cultures but only partially reduced the effect of HS in whole blood. These findings suggest redundant mechanisms in whole blood that may strengthen the immunomodulatory effect of HS in vivo. We conclude that HS resuscitation exerts anti-inflammatory effects that involve panx1, CD39, CD73, and other ectonucleotidases, which produce the adenosine that blocks PMNs by stimulating their A2a receptors. Our findings shed new light on the immunomodulatory mechanisms of HS and suggest possible new strategies to improve the clinical efficacy of hypertonic resuscitation.